2014
DOI: 10.1093/jxb/eru320
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of amino acid metabolic enzymes and transporters in plants

Abstract: Amino acids play several critical roles in plants, from providing the building blocks of proteins to being essential metabolites interacting with many branches of metabolism. They are also important molecules that shuttle organic nitrogen through the plant. Because of this central role in nitrogen metabolism, amino acid biosynthesis, degradation, and transport are tightly regulated to meet demand in response to nitrogen and carbon availability. While much is known about the feedback regulation of the branched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
199
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 318 publications
(208 citation statements)
references
References 233 publications
8
199
1
Order By: Relevance
“…These catabolic enzymes are coregulated at steady state mRNA level under diel and extended darkness conditions as well as during seed development, consistent with the mutant results (Peng et al, 2015;Uygun et al, 2016). While less is known about the importance of genetic regulation of BCAA biosynthetic enzymes, the activities of committed enzymes of the BCAA network are sensitive to in vitro regulation by amino acid products (Less and Galili, 2008;Pratelli and Pilot, 2014). Such allosteric mechanisms could play an important role in BCAA homeostasis; however, relatively little is known about their in vivo importance.…”
Section: Introductionsupporting
confidence: 71%
“…These catabolic enzymes are coregulated at steady state mRNA level under diel and extended darkness conditions as well as during seed development, consistent with the mutant results (Peng et al, 2015;Uygun et al, 2016). While less is known about the importance of genetic regulation of BCAA biosynthetic enzymes, the activities of committed enzymes of the BCAA network are sensitive to in vitro regulation by amino acid products (Less and Galili, 2008;Pratelli and Pilot, 2014). Such allosteric mechanisms could play an important role in BCAA homeostasis; however, relatively little is known about their in vivo importance.…”
Section: Introductionsupporting
confidence: 71%
“…The export of re-mobilized N terminates at the growing leaves (Yoneyama and Sano, 1978). The AAs exported in the phloem (Fukumorita and Chino, 1982) include: (i) actively metabolized AAs and amides, such as glutamine, glutamic acid, asparagine, aspartic acid, and alanine, which are derived from inorganic N assimilation and also produced after active interconversion in the source organs, and (ii) more importantly, coordinately regulated AAs such as lysine, arginine, histidine, valine, tyrosine, phenylalanine, and leucine (Noctor et al, 2002), which are synthesized in the chloroplast under the tight control of feedback-regulation (Pratelli and Pilot, 2014) and are also supplied after protein degradation.…”
Section: Current Knowledge On the Uptake Assimilation And Transportmentioning
confidence: 99%
“…Pratelli and Pilot (2014) suggested that pathogen infection leads to changes in expression of genes involved in amino acid metabolism and transport. They also tabulated the effect of nematode infection on AtAAP gene family members, showing that these responded differentially (induced or repressed) by infection.…”
Section: Introductionmentioning
confidence: 99%